2020
DOI: 10.1186/s12889-020-09655-9
|View full text |Cite
|
Sign up to set email alerts
|

Development and pilot evaluation of a mobile app on parent-child exercises to improve physical activity and psychosocial outcomes of Hong Kong Chinese children

Abstract: Background Parent-child exercises involve children and parents to do workout together and have positive effects on physical and mental health. We developed a mobile app on parent-child exercises called Family Move, which combines coaching videos with game features such as points and level system to enhance the health and wellbeing of both children and parents through parent-child exercises. This pilot pre-post study investigated whether the Family Move app-based intervention had a positive effect on children’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 43 publications
0
44
0
1
Order By: Relevance
“…Moreover, the program incorporated teaching videos with instructions and demonstrations, guiding the parents to engage in physical activities with their children. Meanwhile, each session contained a number of structured game elements, such as points, a level system, ranking, and a scoreboard for tracking progress [ 36 ]. To encourage the participants and make the role modeling effective, live courses were also implemented in the intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the program incorporated teaching videos with instructions and demonstrations, guiding the parents to engage in physical activities with their children. Meanwhile, each session contained a number of structured game elements, such as points, a level system, ranking, and a scoreboard for tracking progress [ 36 ]. To encourage the participants and make the role modeling effective, live courses were also implemented in the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…Parent–child physical activities could be a useful approach to involve both parents and their children with ASD to exercise together, and the fun and joyful time during parent–child physical activity not only brings family together, but also motivates inactive children with ASD to get actively involved and allows both the children and parents to cope with stress [ 35 , 36 ]. To date, there has been a lack of studies on the mental health issues of parents of children with ASD using parent–child dyadic web-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The mean Downs and Black checklist score was 22.6, with the studies ranging between 11 and 28. Out of 15 studies, 8 articles [18,21,23,[26][27][28][29][30]34] were considered high-quality, six studies [19,20,22,25,31,32] moderate quality, and one study [24] poor quality. A breakdown of individual studies is shown in Supplementary Table S1.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Three studies [20,21,31] used both the Xbox Kinect and Wii consoles, one study [24] used only the Wii console, four investigations [19,27,29,32] used only the Xbox Kinect, and one study [26] used the Ps2, Ps3, and Wii consoles. Moreover, four studies [22,23,28,30,34] used applications for smartphone and tablets through which physical activity programs can be forwarded. Two of these apps foresaw the development of the main motor skills, another application physical activity in general, and the last referred to a game.…”
Section: Characteristics Of the Interventionsmentioning
confidence: 99%
“…Además, otros estudios abogan por aplicaciones para promover la actividad física y los hábitos alimentarios saludables dirigidas a toda la familia, de forma que se consiga un cambio de hábitos a nivel individual y familiar y se potencien de este modo sus efectos beneficiosos (288,289). Las aplicaciones diseñadas para el cumplimiento de metas u objetivos (por ejemplo, un número de pasos diarios) y la asignación al usuario de una puntuación determinada en función del nivel de cumplimiento conseguido, podrían ser una opción para la adquisición paulatina de mejores hábitos que permanecieran a largo plazo.…”
Section: Actividad Física En El Transporteunclassified